Tourism and Economic Growth: Assessing the Role of Tourism Industry in Nepal - Pandey, Baikuntha (Cognition, 2025)
Nepal holds significant potential for tourism development. While tourism development can drive economic growth in destination countries, there is ongoing debate about whether tourism directly causes economic growth. This study aims to analyze the trends in inbound tourist arrivals and tourism receipts in Nepal and assess tourism’s impact on Nepal’s economic growth. The study utilizes secondary data spanning from 1975 to 2021, with variables rebased to a common base year of 2010/11. The independent variables include government consumption, gross fixed capital formation, tourism receipts, and trade volume, while the dependent variable is gross domestic product (GDP). A unit root test using the Augmented Dickey-Fuller (ADF) test was conducted to check for stationarity. The Autoregressive Distributed Lag (ARDL) model was employed to examine the impact of the independent variables on the dependent variable. The findings indicate that inbound tourist arrivals in Nepal are rising, and foreign exchange earnings from tourism are also increasing. Most tourists come from India, China, the UK, the USA, and Sri Lanka. The estimated long-run coefficients for government consumption, gross fixed capital formation, and trade volume are positive and statistically significant, indicating a positive relationship with economic growth. However, the study found no long-term relationship between tourism receipts and economic growth.